Patterns of working hour characteristics and risk of sickness absence among shift-working hospital employees: a data-mining cohort study - Rosenström, Tom; Härmä, Mikko; Kivimäki, Mika; Ervasti, Jenni; Virtanen, Marianna; Hakola, Tarja; Koskinen, Aki; Ropponen, Annina (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'Data mining can complement traditional hypothesis-based approaches in characterizing unhealthy work exposures. We used it to derive a hypothesis-free characterization of working hour patterns in shift work and their associations with sickness absence (SA). ' ' METHODS ': 'In this prospective cohort study, complete payroll-based work hours and SA dates were extracted from a shift-scheduling register from 2008 to 2019 on 6029 employees from a hospital district in Southwestern Finland. We applied permutation distribution clustering to time series of successive shift lengths, between-shift rest periods, and shift starting times to identify clusters of similar working hour patterns over time. We examined associations of clusters spanning on average 23 months with SA during the following 23 months. ' ' RESULTS ': 'We identified eight distinct working hour patterns in shift work: (i) regular morning (M)/evening (E) work, weekends off; (ii) irregular M work; (iii) irregular M/E/night (N) work; (iv) regular M work, weekends off; (v) irregular, interrupted M/E/N work; (vi) variable M work, weekends off; (vii) quickly rotating M/E work, non-standard weeks; and (viii) slowly rotating M/E work, non-standard weeks. The associations of these eight working-hour clusters with risk of future SA varied. The cluster of irregular, interrupted M/E/N work was the strongest predictor of increased SA (days per year) with an incidence rate ratio of 1.77 (95% confidence interval 1.74–1.80) compared to regular M/E work, weekends off. ' ' CONCLUSIONS ': 'This data-mining suggests that hypothesis-free approaches can contribute to scientific understanding of healthy working hour characteristics and complement traditional hypothesis-driven approaches.
Keywords: cohort study; data mining; employee scheduling; hospital employee; nurse rostering; occupational health; permutation distribution clustering; shift work; shift worker; sick leave; sickness absence; working hour